Program Studi Pendidikan Bahasa Indonesia, FKIP, Universitas Peradaban - Yulianti, Karina; Wirasti, Kalinaya Dwinda; Arsita, Amalia Dea; Nurlina, Laily (DIALEKTIKA JURNAL PENDIDIKAN BAHASA INDONESIA, 2025)
This study aims to describe the forms of code-mixing that appear in digital communication and analyze the social factors that influence them. The method used is a literature study by reviewing journals and scientific articles published between 2017 and 2025. The results of the study indicate that code-mixing occurs at the word, phrase, and clause levels, in both external (Indonesian-English) and internal (International regional language) forms. The use of code-mixing is influenced by bilingual ability, educational background, group identity, informal communication context, and digital cultural trends. This phenomenon reflects linguistic creativity and the formation of social identity, but still requires attention to prevent it from displacing the function of Indonesian as a unifying language.